A simple and sensitive SERS quantitative analysis method for urea using the dimethylglyoxime product as molecular probes in nanosilver sol substrate. (15th January 2019) - Liang, Aihui; Wang, Haolin; Yao, Dongmei; Jiang, Zhiliang
Highlights: Highly SERS active silver nanosol (AgNP) was prepared by light wave irradiation. Urea reacted with dimethylglyoxime to produce SERS molecular probes. A sensitive SERS quantitative analysis method was developed for urea. Abstract: Under the light wave irradiation, the stable and highly surface enhanced Raman scattering (SERS) active silver nanosol (AgNP) was prepared by reduction of AgNO3, using sodium citrate as reducer. Urea reacted with dimethylglyoxime to produce 4, 5-dimethyl-2-imidazole ketone that exhibited a strong SERS peak at 1320 cm −1 in the as-prepared AgNPs substrate. Under the selected conditions, the increased SERS intensity Δ I was linear to urea concentration in the range of 8.25–825 nM, with a detection limit of 4.92 nM. Accordingly, a new, simple SERS quantitative analysis method for trace urea in foods was established, with relative standard deviation of 0.92–4.8% and recovery of 97.4–101%.